Advances in risk assessment and prophylaxis for central nervous system relapse in diffuse large B-cell lymphoma - David Qualls; Jeremy S. Abramson (Haematologica, 2019)
Central nervous system recurrence of diffuse large B-cell lymphoma is an uncommon but devastating event, making identification of patients at high risk for relapse within the central nervous system essential for clinicians. Modern risk stratification includes both clinical and biological features. A validated clinical risk model employing the five traditional International Prognostic Index risk factors plus renal or adrenal involvement can identify a high-risk patient population with a central nervous system recurrence risk of greater than 10%. Lymphoma involvement of certain discrete extranodal sites such as the testis also confers increased risk, even in stage I disease. Adverse biological risk factors for central nervous system relapse include presence of translocations of MYC, BCL2 and/or BCL6, in so-called double- or triple-hit lymphoma. Immunohistochemically detectable co-expression of MYC and BCL2 in the absence of translocations also portends an increased risk of relapse within the central nervous system, particularly in the setting of the activated B-cell-like subtype of diffuse large B-cell lymphoma. The role, method, and timing of prophylactic therapy remain controversial based on the available data. We review both intrathecal and systemic strategies for prophylaxis in high-risk patients. Our preference is for systemic methotrexate in concert with standard chemoimmunotherapy in the majority of cases. Several novel agents have also demonstrated clinical activity in primary and secondary central nervous system lymphoma and warrant future investigation in the prophylactic setting.